Pengaruh Kecepatan Putar Disk Mill Terhadap Karakteristik Tepung dari 3 Jenis Polong - Adipa, Rakha; Tamrin, Tamrin; Rahmawati, Winda; Suharyatun, Siti (abe.fp.unila.ac.id, 2022)
Soybeans and mung beans are legumes that can be processed into various types of food or complementary foods. One of the processed products made from soybeans or mung bean which can be used as a half product is soybean flour or mung bean flour. This study aims to analyze the effect of differences in RPM on the performance of the disc mill for grinding flour products and the level of fineness of the resulting flour products. The study used a Factorial Completely Randomized Design (CRD) which consisted of 2 factors, namely the rotational speed (RPM) and the material. The rotational speed consists of 3 treatment levels, namely 1186 RPM (R1), 1862 RPM (R2), 2495 RPM (R3). The type of material consists of yellow soybeans (K1), black soybeans (K2) and mung beans (K3). The research parameters consisted of flouring capacity, flour moisture content, flour yield and flour fineness. The data were analyzed using the ANOVA test, followed by the BNT test at a significance level of = 5%. The results showed that RPM and material affected the flouring capacity, moisture content and flour yield. The highest flouring capacity was flouring mung beans with a speed of 2495 RPM (R3K3) of 41.77 kg/hour, while the lowest capacity was at a rotational speed of 1186 RPM. for yellow, black and green soybeans. The water content of mung bean flour (10.87%) was higher than that of yellow and black soybean flour. The level of fineness at RPM 2495 on yellow soybeans, black soybeans and green beans produces flour with a medium fineness level. Keywords: Flouring Capacity, Level of Fineness, Mung Bean Flour, Soybean Flour, Yield.